Isolation And Sequence Analysis Of Candidate Cdna Involved In Carotenoid Biosynthesis In The Flavedo Tissue Of Pummelo (Citrus Grandis L. Osbeck) - Hanapi, Ummi Kalthum (2008)
Citrus grandis L. Osbeck (pummelo) was recognized as one of the potential fruit to be commercialized under the goal of the Third National Agricultural Plan’s (DPN3, 1998-2010). However, the pale yellowish green colour of C. grandis fruit flavedo rendered is unattractive and has less market demand compared to other citrus vaireties. Carotenoid biosynthesis has been well studied and recognized to be the main pathway which contributes to the formation of colour in the flavedo of most citrus fruit. However, there is still limited information currently available on carotenoid biosynthesis in green pigmented citrus fruit flavedo. To increase the market demand, locally and overseas, there is a need to modify the colour of C. grandis from pale yellowish green to more attractive colour like other citrus. Therefore, the study was initiated to explore the possibility of modifying fruit flavedo colour through the use of molecular techniques. Thus, it is necessary to isolate and sequence the genes involved in carotenoid pathway of green flavedo of citrus fruit. In this study, comparative analysis of the sequences isolated from the gene of green flavedo will be compared with orange pigmented citrus, other plants and bacteria which contain high carotenoids. The study began with tagging of open pollinated flowers (that showed indication of fruit formation to ensure the right stage of maturation), followed by genomic DNA and total RNA isolation prior to further molecular analyses, such as PCR and RTPCR. The primers used in this study were designed based on the sequence information obtained from the Genbank database. The four genes which are involved in carotenoid biosynthesis and responsible for the orange pigmentation in citrus fruit viz. phytoene synthase (psy, 0.46 kb), phytoene desaturase (pds, 1.11 kb), lycopene β-cyclase (lyc, 0.70 kb) and β-carotene hydroxylase (chx, 0.23 kb), were isolated via PCR and RTPCR. From sequence analysis, psy, pds, lyc and chx showed high similarities with the corresponding genes in citrus varieties, Prunus armeniaca and Capsicum annuum. A full sequence of chx gene was isolated from cDNA library of C. grandis fruit flavedo. The 1268 bp of chx gene consisted of an open reading frame (ORF) of 271 codons (mass of 65.8 kD) and 170-nucleotide 5’ untranslated sequences was isolated. Compared to other organisms, seven histidine residues which were present in C. grandis chx were also found to be conserved in Alcaligenes sp (accession no. D58422), Agrobacterium aurianticum (accession no. D58420), Erwinia herbicola (accession no. M87280) and Pseudomonas putida (accession no. KT2440 NP_745389). ‘Motif 1’ and the predicted ‘TM helix’ regions were also observed in C. grandis when compared to Prochlorococcus marinus MED4 CrtL-ε (CAE19092), Lycopersicon esculentum Lcy-ε (O65837), Tagetes erecta Lcy-ε (AAG10428), Capsicum annuum Lcy-β (Q43415) and Arabidopsis thaliana Lcy-β (AAA81880). In conclusion, psy, pds, lyc and a full length of chx have been successfully isolated the flavedo of C. grandis.The sequences of these genes were found to be highly conserved with the corresponding gene in other plants especially in citrus varieties.